STUDI DEKOMPOSISI TERMAL PIROLISIS Spirulina platensis DENGAN LAJU PEMANASAN 15 °C/MENIT - Utami, Devira Ulva; Subagyono, RR Dirgarini Julia Nurlianti; Gunawan, Rahmat (PROSIDING SEMINAR KIMIA, 2024)
Thermal decomposition study of Spirulina platensis pyrolysis with heating rate of 15°C/min was conducted. Microalgae pyrolysis was carried out with a thermogravimetric analyzer (TGA) instrument. This research focused on analyzing the thermal decomposition process of Spirulina platensis which has a moisture content of 8.34% and ash content of 7.18%. Thermal decomposition of Spirulina platensis occurs in 3 stages, namely water evaporation at temperatures ≤ 140°C; active pyrolysis with a temperature range of ±147-502°C involving thermal decomposition of carbohydrate compounds, proteins and lipids; and passive pyrolysis with temperatures ≥ 502°C, where the remains of more stable organic components were decomposed. Keywords: Spirulina platensis, thermogravimetric analysis, and decomposition